Effects of curcumin on oxidative stress, inflammation and apoptosis in L-arginine induced acute pancreatitis in mice - Prasong Siriviriyakul; Thidarat Chingchit; Naruemon Klaikeaw; Maneerat Chayanupatkul; Duangporn Werawatganon (Heliyon, 2019)
Background and purpose: Curcumin, an active constituent of rhizomes of Curcuma longa Linn, exhibits a variety of biological activities such as anti-inflammation and anti-oxidant. The present study aims to examine the effects of curcumin on oxidative stress, inflammation and apoptosis in L-arginine induced acute pancreatitis (AP) in mice. Methods: Male ICR mice were randomly divided into 4 groups. Control group received intraperitoneal injection (i.p.) of 1% DMSO as a vehicle. AP group received two doses of i.p. L-arginine (L-Arg) 450 mg/100 g body weight (BW) at 1-hour interval. AP plus low-dose curcumin group received i.p. curcumin 50 mg/kg BW 1 hour before L-Arg injection and then once daily for 3 days. AP plus high-dose curcumin group received i.p. curcumin 200 mg/kg BW 1 hour before L-Arg injection and then once daily for 3 days. All mice were sacrificed at 72 hours. Pancreatic tissue was obtained for histological evaluation, immunohistochemical studies for nuclear factor-kappa beta (NF-kβ), apoptosis and myeloperoxidase (MPO), and Western blot analyses for 4-Hydroxynonenal (4-HNE). Blood samples were collected for amylase analysis. Results: Mean body weight was significantly lower in AP group than in control group, while in curcumin group, body weight was maintained. The serum amylase, number of MPO positive cells, NF-kB positive cells, TUNEL positive cells, and 4-HNE expression significantly increased in AP group when compared with control group, but decreased in low and high-dose curcumin groups. Mice in AP group developed severe pancreatic inflammation, edema and fat necrosis. While mice in low and high-dose curcumin groups showed a significant improvement in histopathological scores. There was no significant difference between low and high doses of curcumin. Conclusion: Curcumin could attenuate acute pancreatitis via anti-oxidant, anti-inflammation and anti-apoptosis property leading to the improvement in pancreatic damage.